Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve for \( (f+g)(x) \) where \( f(x) = -5^x - 4 \) and \( g(x) = -3x - 2 \), we need to find the sum of these two functions:
1. Start with the functions given:
[tex]\[ f(x) = -5^x - 4 \][/tex]
[tex]\[ g(x) = -3x - 2 \][/tex]
2. To find \( (f+g)(x) \), we add \( f(x) \) and \( g(x) \):
[tex]\[ (f+g)(x) = f(x) + g(x) \][/tex]
3. Substitute the expressions for \( f(x) \) and \( g(x) \) into the equation:
[tex]\[ (f+g)(x) = (-5^x - 4) + (-3x - 2) \][/tex]
4. Combine the terms:
[tex]\[ (f+g)(x) = -5^x - 4 - 3x - 2 \][/tex]
5. Simplify the expression by combining the constants:
[tex]\[ (f+g)(x) = -5^x - 3x - 6 \][/tex]
Looking at the options provided:
A. \((f+g)(x) = -5^x - 7x - 2\)
B. \((f+g)(x) = 5^x + 3x + 6\)
C. \((f+g)(x) = -8x - 6\)
D. \((f+g)(x) = -5^x - 3x - 6\)
The correct answer matches the expression we derived:
[tex]\[ (f+g)(x) = -5^x - 3x - 6 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{D} \][/tex]
1. Start with the functions given:
[tex]\[ f(x) = -5^x - 4 \][/tex]
[tex]\[ g(x) = -3x - 2 \][/tex]
2. To find \( (f+g)(x) \), we add \( f(x) \) and \( g(x) \):
[tex]\[ (f+g)(x) = f(x) + g(x) \][/tex]
3. Substitute the expressions for \( f(x) \) and \( g(x) \) into the equation:
[tex]\[ (f+g)(x) = (-5^x - 4) + (-3x - 2) \][/tex]
4. Combine the terms:
[tex]\[ (f+g)(x) = -5^x - 4 - 3x - 2 \][/tex]
5. Simplify the expression by combining the constants:
[tex]\[ (f+g)(x) = -5^x - 3x - 6 \][/tex]
Looking at the options provided:
A. \((f+g)(x) = -5^x - 7x - 2\)
B. \((f+g)(x) = 5^x + 3x + 6\)
C. \((f+g)(x) = -8x - 6\)
D. \((f+g)(x) = -5^x - 3x - 6\)
The correct answer matches the expression we derived:
[tex]\[ (f+g)(x) = -5^x - 3x - 6 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{D} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.